Water-soluble film, drug packaging body, and method for producing drug packaging body

By adjusting the elastic modulus of the polyvinyl alcohol-based resin and using plasticizers and modified PVA-based resins, a water-soluble film with excellent mold following is prepared, which solves the problem of poor appearance during molding of the packaging body in the prior art, and achieves high-quality packaging body molding.

CN119546675APending Publication Date: 2025-02-28MITSUBISHI CHEM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380053004.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2023-07-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing water-soluble films have poor following the mold during molding, resulting in uneven tension, deformation of the packaging body, or wrinkles, and poor appearance.

Method used

By adjusting the elastic modulus of the polyvinyl alcohol-based resin, using a plasticizer and a modified PVA-based resin, a water-soluble film with an initial elastic modulus of 2.5 to 10 MPa was prepared. The film shows excellent following in deep-drawn, complex-shaped molds.

Benefits of technology

It achieves excellent appearance of the packaging body with tension, deformation and wrinkles, ensuring the molding quality and use effect of the packaging body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236226580000081
    Figure BDA0005236226580000081
  • Figure BDA0005236226580000082
    Figure BDA0005236226580000082
  • Figure BDA0005236226580000083
    Figure BDA0005236226580000083
Patent Text Reader

Abstract

Provided is a polyvinyl alcohol-based water-soluble film which has excellent followability to a mold during molding and which can be molded into a package having an excellent appearance. The water-soluble film is characterized in that the water-soluble film contains a polyvinyl alcohol-based resin (A), and the initial elastic modulus obtained by a tensile creep test using a dynamic viscoelasticity measurement device is 2.5-10 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water-soluble film and a drug packaging body with a polyvinyl alcohol resin as a main component. More specifically, it relates to: when a liquid detergent or other drug is packaged to form a packaging body, the water-soluble film and the drug packaging body have excellent mold followability during molding and can be molded into a packaging body with excellent appearance, and a method for manufacturing the same. Background Art

[0002] Polyvinyl alcohol-based films are thermoplastic resins that are water-soluble polyvinyl alcohol-based resins. They have been used in a wide range of fields as water-soluble films characterized by their water solubility in water, making full use of the water solubility of polyvinyl alcohol. Specifically, they are used for packaging (unit packaging) of pesticides, detergents and other drugs, (hydraulic) transfer films, sanitary products such as napkins and diapers, pollutant treatment products such as ostomy bags, medical products such as blood-absorbing sheets, and temporary substrates such as seedling sheets, seed tapes and embroidery base fabrics.

[0003] Among these, unit packaging of pesticides, detergents and other chemicals not only saves time by not having to measure the dosage each time when using, but also has the advantage of not contaminating hands. In particular, the use of unit packaging (individual packaging) for liquid products such as liquid detergents is expanding.

[0004] For example, a water-soluble film suitable for thermoforming deep-drawn profiles and used in packaging of household care compositions such as detergents and dishwashing detergents has been proposed (for example, see Patent Document 1).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2017 / 132540 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] Such an independent package usually has one or more partitions, including various shapes and sizes. In recent years, in particular, in the independent packaging of liquid detergents, from the perspective of improving the cleaning effect and appearance, packaging bodies with partitions of more complex shapes and sizes have been designed, and in order to form such independent packages, deep drawing and complex shape molds are used for molding.

[0010] However, when molding is performed using conventional water-soluble films, the film has poor followability to the mold, the resulting package has poor tension, or the shape is deformed or wrinkled, resulting in poor appearance, and further improvements are required.

[0011] Therefore, in such a background, the present invention provides: a water-soluble film which has excellent followability to a mold during molding and can be molded into a package body with excellent appearance when packaging a liquid detergent or other medicine to form a package body, and a medicine package body formed by packaging various medicines with the water-soluble film. In addition, a method for manufacturing the medicine package body is also provided.

[0012] Solutions for solving problems

[0013] However, in view of the above situation, the inventors have conducted in-depth research and found that: focusing on the relationship between the followability of the film to the mold during packaging molding and the elastic modulus of the film, the initial elastic modulus obtained by the creep test is set to a specific range, so that a water-soluble film with excellent followability can be obtained even in deep drawing and complex shape molds, and by using the above-mentioned water-soluble film to form a packaging body, a packaging body with excellent appearance, without tension, deformation, and wrinkles can be obtained.

[0014] That is, the gist of the present invention is as follows. [1]

[0016] A water-soluble film, characterized in that it is a water-soluble film containing a polyvinyl alcohol-based resin (A), and the initial elastic modulus obtained by a tensile creep test using a dynamic viscoelasticity measuring device is 2.5 to 10 MPa. [2]

[0018] The water-soluble film according to [1], further comprising a plasticizer (B), wherein the content of the plasticizer (B) is 3 to 25 parts by mass based on 100 parts by mass of the polyvinyl alcohol-based resin (A). [3]

[0020] The water-soluble film according to [1] or [2], wherein the polyvinyl alcohol-based resin (A) contains an anionic group-modified polyvinyl alcohol-based resin. [4]

[0022] The water-soluble film according to any one of [1] to [3] is characterized in that the polyvinyl alcohol-based resin (A) contains a polyvinyl alcohol-based resin (a1) which is the main component of the component (A) and a polyvinyl alcohol-based resin (a2) which satisfies the following (α) in relationship with the component (a1).

[0023] (α) The viscosity of a 4 mass % aqueous solution of the polyvinyl alcohol-based resin (a2) at 20°C is higher than the viscosity of a 4 mass % aqueous solution of the polyvinyl alcohol-based resin (a1) at 20°C. [5]

[0025] The water-soluble film according to [4], wherein the polyvinyl alcohol-based resin (a1) is a modified polyvinyl alcohol-based resin. [6]

[0027] A medicine package, comprising: a package formed of the water-soluble film according to any one of [1] to [5], and a medicine packaged in the package. [7]

[0029] The drug packaging body according to [6] is characterized in that the drug packaging body has a plurality of partitions, and the drug is packaged in at least one of the partitions. [8]

[0031] The drug package according to [6] or [7] is characterized in that the drug is a liquid detergent. [9]

[0033] A method for manufacturing a drug packaging body, characterized in that it is a method for manufacturing a drug packaging body using two or more water-soluble films, in which a first water-soluble film is vacuum-formed using a mold, a drug is added to the first water-soluble film formed by the aforementioned vacuum forming, and the aforementioned formed first water-soluble film is bonded to a second water-soluble film to package the drug to manufacture the drug packaging body, wherein the aforementioned first water-soluble film is a water-soluble film described in any one of [1] to [5].

[10]

[0035] The method for manufacturing a drug packaging body according to [9] is characterized in that the thickness of the thinnest portion of the first water-soluble film formed by the vacuum forming is less than 35% of the thickness of the first water-soluble film before the vacuum forming.

[0036] Effects of the Invention

[0037] When packaging liquid detergents and other drugs, the water-soluble film of the present invention has excellent followability to a mold during molding, and can be molded into a package body with excellent appearance having tension, no deformation, and no wrinkles. DETAILED DESCRIPTION

[0038] In the present specification, when “X to Y” (X and Y are arbitrary numbers) is expressed, unless otherwise stated, it also includes the meaning of “X or more and Y or less”, and the meaning of “preferably greater than X” or “preferably less than Y”.

[0039] In addition, “X and / or Y (X, Y are arbitrary structures)” means at least one of X and Y, and has three meanings: only X, only Y, and X and Y.

[0040] In addition, polyvinyl alcohol is sometimes abbreviated as "PVA", a film containing a polyvinyl alcohol resin as a main component is sometimes abbreviated as "PVA film", and a water-soluble film containing a polyvinyl alcohol resin as a main component is sometimes abbreviated as "PVA water-soluble film".

[0041] Hereinafter, the present invention will be described in detail.

[0042] A water-soluble film according to one embodiment of the present invention (hereinafter sometimes referred to as "the present water-soluble film") is characterized in that it is a water-soluble film containing a polyvinyl alcohol-based resin (A) and has an initial elastic modulus of 2.5 to 10 MPa obtained by a tensile creep test using a dynamic viscoelasticity measuring apparatus.

[0043] Here, in the present invention, the initial elastic modulus obtained by performing a tensile creep test using a dynamic viscoelasticity measuring device is a value measured and calculated as follows. That is, a water-soluble film left to stand for 24 hours at 23°C and 40% RH is cut into a sample having a length of 60 mm in the flow direction (MD) and 5 mm in the width direction (TD). The value is calculated by measuring the elastic modulus of the obtained sample using a dynamic viscoelasticity measuring device "DMAQ800" (manufactured by TA Instruments Japan) under the following setting conditions.

[0044] [Setting conditions]

[0045] Chuck spacing: 5mm

[0046] Film width: 5mm

[0047] Measurement (setting) temperature: 30°C

[0048] Measurement mode: DMACreep

[0049] Load: 16.1MPa

[0050] Hold time: 0.5 minutes

[0051] Cool-down time: 5 minutes

[0052] [Calculation method]

[0053] The initial (0.004 minutes after the start of the measurement) elastic modulus (MPa) is calculated using the following method. That is, the strain (ε) is calculated based on the length of the film at the start of the measurement (L0) and the length of the film 0.004 minutes after the start of the measurement (L) (strain (ε) = (L-L0) × 100 / L0). Here, the elastic modulus is calculated using the obtained strain (ε) and the set load of 16.1 MPa. (Elastic modulus (MPa) = 16.1 / strain (ε)).

[0054] From the viewpoint of improving the followability of the mold during molding and obtaining a packaging body with excellent appearance with tension, no deformation, and no wrinkles, it is important that the initial elastic modulus of the water-soluble film obtained by tensile creep test using a dynamic viscoelasticity measuring device is 2.5 to 10.0 MPa. The above elastic modulus is preferably 3.0 to 9.0 MPa, particularly preferably 3.5 to 8.0 MPa, further preferably 3.8 to 7.5 MPa, and particularly preferably 4.0 to 7.0 MPa. When the above elastic modulus is too large, the followability of the film to the mold during molding is insufficient, so the molded body of the desired shape cannot be obtained, and there is a tendency for the appearance of the packaging body to deteriorate. In addition, when the above elastic modulus is too small, there is a tendency that the mechanical properties of the film are low, the packaging body is prone to bag breakage, and sufficient compression strength cannot be obtained.

[0055] Hereinafter, each component constituting the present water-soluble film will be described.

[0056] [PVA-based resin (A)]

[0057] The present water-soluble film is a water-soluble film with a PVA-based resin (A) as the main component. Here, the PVA-based resin (A) as the main component means that the PVA-based resin (A) generally contains 50% by mass or more, preferably 55% by mass or more, and particularly preferably 60% by mass or more relative to the entire water-soluble film. When the above content is too little, there is a tendency for the solubility in water and the mechanical properties of the film to decrease. The upper limit of the above content is generally 99% by mass or less, preferably 95% by mass or less, and particularly preferably 90% by mass or less, from the perspective of the shape stability over time when the liquid detergent packaging body is made.

[0058] It should be noted that "water-soluble film" means a film that dissolves in water at about room temperature (20°C). In the present invention, the solubility of the film can be evaluated as follows. The water-soluble film is cut into a size of 3 cm × 5 cm, placed in a 1-liter beaker filled with water (1 liter), fixed with a clamp, the water temperature is maintained at 20°C and stirred by a stirrer (rotor length 3 cm, rotation speed 750 rpm), and the film is considered dissolved if no dispersion of insoluble particles with a diameter of more than 1 mm is observed by visual inspection.

[0059] Examples of the PVA-based resin (A) used in the present water-soluble film include unmodified PVA and modified PVA-based resins.

[0060] Unmodified PVA and modified PVA-based resins can be produced using a production method known in the technical field, and can be produced, for example, as follows.

[0061] Unmodified PVA can be produced by saponifying a vinyl ester polymer obtained by polymerizing a vinyl ester compound.

[0062] Examples of the vinyl ester compounds include vinyl formate, vinyl acetate, vinyl trifluoroacetate, vinyl propionate, vinyl butyrate, vinyl caprate, vinyl laurate, vinyl versatate, vinyl palmitate, and vinyl stearate, and vinyl acetate is preferably used. The vinyl ester compounds may be used alone or in combination of two or more.

[0063] The modified PVA-based resin can be produced by copolymerizing the aforementioned vinyl ester-based compound with an unsaturated monomer copolymerizable with the vinyl ester-based compound and then saponifying the copolymer.

[0064] Examples of unsaturated monomers copolymerizable with the vinyl ester compounds include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl-containing α-olefins such as 3-butene-1-ol, 4-pentene-1-ol, and 5-hexene-1-ol, and their acylated derivatives; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid, and their salts, monoesters, or dialkyl esters; amides such as diacetone acrylamide, acrylamide, and methacrylamide; olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methyl allyl sulfonic acid, and their salts; N-vinyl pyrrolidone, etc. These may be used alone or in combination of two or more.

[0065] In addition, as modified PVA-based resins, for example, those having primary hydroxyl groups in the side chains can be listed. For example, the number of primary hydroxyl groups in the side chains is usually 1 to 5, preferably 1 to 2, and particularly preferably 1. Furthermore, in addition to the primary hydroxyl groups, secondary hydroxyl groups are also preferably present. As the above-mentioned modified PVA-based resins, for example, PVA-based resins having hydroxyalkyl groups in the side chains and PVA-based resins having 1,2-diol structural units in the side chains can be listed. The PVA-based resin having 1,2-diol structural units in the side chains can be produced, for example, by the following methods: (1) a method of saponifying a copolymer of vinyl acetate and 3,4-diacetoxy-1-butene; (2) a method of saponifying and decarbonating a copolymer of vinyl acetate and vinyl ethylene carbonate; (3) a method of saponifying and deketalizing a copolymer of vinyl acetate and 2,2-dialkyl-4-vinyl-1,3-dioxolane; (4) a method of saponifying a copolymer of vinyl acetate and glycerol monoallyl ether, etc.

[0066] As the modified PVA resin used in this water-soluble film, from the aspect of solubility, it is preferably modified by at least one hydrophilic group selected from carboxyl, sulfonic acid group, phosphoric acid group, pyrrolidone ring group, etc. It should be noted that these modifying groups also include salts such as sodium and potassium of these functional groups. Among them, it is preferred to use anionic group-modified PVA resin, as the type of anionic group, for example, carboxyl, sulfonic acid group, phosphoric acid group, etc. can be listed, from the aspect of solubility stability over time, carboxyl and sulfonic acid group are particularly preferred, and carboxyl is further preferred.

[0067] The above-mentioned carboxyl-modified PVA-based resin can be manufactured by any method. As the manufacturing method, for example, the following methods can be listed: (i) a method of copolymerizing an unsaturated monomer having a carboxyl group with a vinyl ester-based compound and then saponifying it, (ii) a method of using an alcohol, aldehyde or thiol having a carboxyl group as a chain transfer agent to coexist and polymerize the vinyl ester-based compound and then saponify it, etc.

[0068] Examples of the unsaturated monomer having a carboxyl group in the method (i) include ethylenically unsaturated dicarboxylic acids (maleic acid, fumaric acid, itaconic acid, etc.), or ethylenically unsaturated dicarboxylic acid monoesters (maleic acid monoalkyl esters, fumaric acid monoalkyl esters, itaconic acid monoalkyl esters, etc.), or ethylenically unsaturated dicarboxylic acid diesters (maleic acid dialkyl esters, fumaric acid dialkyl esters, itaconic acid dialkyl esters, etc.) [wherein these diesters need to be converted into carboxyl groups by hydrolysis during the saponification of the copolymer], or ethylenically unsaturated carboxylic acids. Monomers such as maleic anhydride (maleic anhydride, itaconic anhydride, etc.), or ethylenically unsaturated monocarboxylic acids ((meth)acrylic acid, crotonic acid, etc.) and their salts are preferably used, among which maleic acid, maleic acid monoalkyl esters, maleic acid dialkyl esters, maleate salts, maleic anhydride, itaconic acid, itaconic acid monoalkyl esters, itaconic acid dialkyl esters, (meth)acrylic acid, etc. are preferably used, and maleic acid, maleic acid monoalkyl esters, maleic acid dialkyl esters, maleate salts, maleic anhydride are particularly preferably used, and maleic acid monoalkyl esters are further preferably used. These can be used alone or in combination of two or more.

[0069] In the method (ii) described above, compounds derived from mercaptans having a large chain transfer effect are particularly effective, and examples thereof include compounds represented by the following general formulas (1) to (3).

[0070]

[0071] [In the above general formula (1), n ​​is an integer of 0 to 5.]

[0072]

[0073] [In the above general formula (2), n is an integer of 0 to 5. In addition, R1, R2, and R3 each represent a hydrogen atom or a lower alkyl group (which may contain a substituent).]

[0074]

[0075] [In the above general formula (3), n is an integer of 0 to 20.]

[0076] In addition, salts of the compounds represented by the above general formulae (1) to (3) may also be mentioned. Specifically, for example, thioglycolate, 2-mercaptopropionate, 3-mercaptopropionate, 2-mercaptostearate, etc. may be mentioned. These compounds may be used alone or in combination of two or more.

[0077] It should be noted that, in addition to the aforementioned unsaturated monomers and vinyl ester compounds having a carboxyl group, other common monomers may be contained within the range that does not impair water solubility for polymerization, and as these monomers, for example, alkyl esters of ethylenically unsaturated carboxylic acids, allyl esters of saturated carboxylic acids, α-olefins, alkyl vinyl ethers, alkyl allyl ethers, (meth) acrylamide, (meth) acrylonitrile, styrene, vinyl chloride, etc. may be used. These may be used alone or in combination of two or more.

[0078] In addition, the method for producing the aforementioned carboxyl-modified PVA-based resin is not limited to the aforementioned method. For example, a method in which a carboxyl-containing compound having a functional group reactive with a hydroxyl group, such as a dicarboxylic acid, an aldehyde carboxylic acid, or a hydroxycarboxylic acid, is subjected to a post-reaction with a PVA-based resin (partially saponified or completely saponified).

[0079] In addition, when using a sulfonic acid-modified PVA-based resin obtained by modification with a sulfonic acid group, it can be produced, for example, by the following methods: a method in which copolymerization components such as vinyl sulfonic acid, styrene sulfonic acid, allyl sulfonic acid, methallyl sulfonic acid, and 2-acrylamide-2-methylpropane sulfonic acid are copolymerized with a vinyl ester compound and then saponified; a method in which vinyl sulfonic acid or its salt, 2-acrylamide-2-methylpropane sulfonic acid or its salt, etc. are subjected to Michael addition to a PVA-based resin; and the like.

[0080] On the other hand, examples of methods for post-modifying the unmodified PVA include methods of acetoacetylating, acetalizing, aminating, etherifying, grafting, phosphate-esterifying, and oxyalkylene-esterifying the unmodified PVA.

[0081] In the present water-soluble film, from the perspective of improving the solubility of the film in water, especially the solubility in cold water (for example, below 10°C), or suppressing the decrease in solubility over time when the packaged substance is an alkaline substance, it is preferred to contain a modified PVA-based resin, particularly preferably a PVA-based resin modified with anionic groups, and further preferably a PVA-based resin modified with carboxyl groups.

[0082] When a carboxyl-modified PVA-based resin is used in the present water-soluble film, maleic acid-modified PVA-based resin and itaconic acid-modified PVA-based resin are preferred from the aspects of operability, high polymerizability with vinyl ester-based monomers and excellent productivity. In particular, from the aspect of the temporal stability of the solubility of the film when the drug is packaged (especially the aspect that it is not affected by the pH of the drug), maleic acid-modified PVA-based resin is preferred.

[0083] The average saponification degree of the PVA-based resin (A) is preferably 80 mol% or more, particularly preferably 82 to 99.9 mol%, further preferably 85 to 98.5 mol%, and particularly preferably 90 to 97 mol%. If the above average saponification degree is too low, the solubility of the film in water tends to decrease. Even if the average saponification degree is too large, the water solubility tends to decrease. In addition, from the perspective of the balance between solubility and excellent moldability (mold following), the average saponification degree is more preferably 90 to 99.9 mol%, particularly preferably 91 to 98.5 mol%, and further preferably 92 to 97 mol%.

[0084] It should be noted that the average saponification degree of the aforementioned PVA-based resin (A) means that the average saponification degree of the entire PVA-based resin contained in the PVA-based water-soluble film is within these ranges. When the PVA-based water-soluble film contains multiple PVA-based resins, the average saponification degree of the entire PVA-based resin (A) is obtained by using the ratio and average saponification degree of each PVA-based resin contained in the entire PVA-based resin (A) and using the following formula.

[0085] (Formula) Average saponification degree of the entire PVA resin (A) = content ratio of PVA resin (i) × average saponification degree of PVA resin (i) + content ratio of PVA resin (ii) × average saponification degree of PVA resin (ii) + ...

[0086] In particular, when unmodified PVA is used as the PVA-based resin (A), the average saponification degree is preferably 80 mol% or more, particularly preferably 82 to 99 mol%, and further preferably 85 to 90 mol%. When the average saponification degree is too low, the water solubility, especially the solubility over time of a film in which a medicine is packaged, tends to decrease. It should be noted that even if the average saponification degree is too high, the solubility in water tends to decrease.

[0087] On the other hand, when a modified PVA resin is used as the PVA resin (A), the average saponification degree is preferably 80 mol% or more, particularly preferably 85 to 99.9 mol%, and further preferably 90 to 98 mol%. When the average saponification degree is too low, the solubility of the film, especially the solubility of the film when a medicine is packaged, tends to decrease over time. It should be noted that even if the average saponification degree is too high, the solubility in water tends to decrease.

[0088] Furthermore, when an anionic group-modified PVA resin is used as the PVA resin (A), the average saponification degree is preferably 85 mol% or more, particularly preferably 88 to 99 mol%, further preferably 90 to 98 mol%, and particularly preferably 92 to 97 mol%. When the saponification degree is within this range, the reduction in the solubility of the film over time is suppressed and the moldability becomes more excellent. When the above average saponification degree is too small, there is a tendency that the solubility of the water-soluble film in water decreases over time due to the pH of the drug to be packaged. It should be noted that when the average saponification degree is too large, there is a tendency that the solubility in water decreases.

[0089] The above-mentioned average saponification degree is measured in accordance with JIS K 6726 3.5.

[0090] The degree of polymerization of the aforementioned PVA-based resin (A) used in the present water-soluble film can generally be expressed by the viscosity of the aqueous solution, and the viscosity of a 4% by mass aqueous solution at 20°C is preferably 5 to 55 mPa·s, more preferably 10 to 50 mPa·s, particularly preferably 15 to 45 mPa·s, particularly preferably 17 to 43 mPa·s, 21 to 40 mPa·s, and further preferably 21.5 to 38 mPa·s.

[0091] It should be noted that the 4 mass % aqueous solution viscosity at 20°C of the aforementioned PVA-based resin (A) means that the 4 mass % aqueous solution viscosity at 20°C of the entire PVA-based resin contained in the PVA-based water-soluble film is within these ranges. When the water-soluble film contains a plurality of PVA-based resins, the 4 mass % aqueous solution viscosity at 20°C of the entire PVA-based resin (A) is obtained using the ratio of each PVA-based resin contained in the entire PVA-based resin (A) and the 4 mass % aqueous solution viscosity at 20°C and the following formula.

[0092] (Formula) 4 mass % aqueous solution viscosity of the entire PVA resin (A) at 20°C = content ratio of PVA resin (i) × 4 mass % aqueous solution viscosity of PVA resin (i) at 20°C + content ratio of PVA resin (ii) × 4 mass % aqueous solution viscosity of PVA resin (ii) at 20°C + ...

[0093] When unmodified PVA is used as the PVA-based resin (A), the viscosity of a 4 mass % aqueous solution at 20° C. is preferably 5 to 60 mPa·s, more preferably 10 to 50 mPa·s, and particularly preferably 15 to 45 mPa·s.

[0094] In addition, when a modified PVA-based resin is used as the PVA-based resin (A), the viscosity of a 4 mass % aqueous solution at 20°C is preferably 5 to 50 mPa·s, more preferably 15 to 45 mPa·s, particularly preferably 17 to 40 mPa·s, particularly preferably 21 to 38 mPa·s, and further preferably 21.5 to 35 mPa·s.

[0095] When the viscosity is within this range, the mechanical strength of the water-soluble film is excellent and the formability is also excellent. If the viscosity is too low, the mechanical strength of the water-soluble film as a packaging material tends to decrease, while if it is too high, the productivity tends to decrease.

[0096] The viscosity of the 4 mass % aqueous solution is measured in accordance with JIS K 6726 3.11.2.

[0097] The modification amount of the modified PVA resin is preferably 1 to 15 mol%, particularly preferably 1.5 to 12 mol%, and further preferably 2 to 8 mol%. When the modification amount is too small, the solubility in water tends to decrease, and when it is too large, the productivity of the PVA resin tends to decrease, the biodegradability tends to decrease, and there is also a tendency to cause blocking.

[0098] In the present water-soluble film, the aforementioned PVA-based resins (A) may be used individually, or two or more types having at least one different saponification degree, viscosity, modification type, modification amount, etc. may be used in combination. For example, two or more unmodified PVAs may be used in combination, two or more modified PVA-based resins may be used in combination, or one or more unmodified PVA and one or more modified PVA-based resins may be used in combination.

[0099] Among them, from the aspect of solubility, the PVA-based resin (A) preferably contains a modified PVA-based resin. From the aspect of water sealing properties and compressive strength when made into a packaging body, it is preferred to use a combination of one or more unmodified PVA and modified PVA-based resins, and it is particularly preferred to use a combination of one or more unmodified PVA and anionic group-modified PVA-based resins.

[0100] In addition, from the perspective of suppressing excessive dissolution of the packaging body and further improving the followability during film molding, it is preferred to contain two or more PVA-based resins having different viscosities of a 4 mass % aqueous solution at 20°C. Furthermore, as the above-mentioned two or more PVA-based resins, it is preferred to contain a first PVA-based resin (a1) as the main component and a second PVA-based resin (a2) that satisfies the following (α) in relationship with the aforementioned first PVA-based resin (a1).

[0101] (α) The 4 mass % aqueous solution viscosity (V2) of the PVA-based resin (a2) at 20°C is higher than the 4 mass % aqueous solution viscosity (V1) of the PVA-based resin (a1) at 20°C (V2>V1).

[0102] From the perspective of suppressing excessive dissolution of the package and the followability during film molding, it is particularly preferred that the difference in viscosity of the 4 mass % aqueous solution of the first PVA-based resin (a1) and the second PVA-based resin (a2) at 20°C (|V2-V1|) is 1.5 mPa·s or more, particularly preferably 2 mPa·s or more, 3 mPa·s or more, 5 mPa·s or more, 10 mPa·s or more, and more preferably greater than 10 mPa·s. The upper limit of the viscosity difference is preferably 35 mPa·s or less, preferably 30 mPa·s or less, and more preferably 25 mPa·s or less.

[0103] In addition, the first PVA-based resin (a1) serving as the above-mentioned main component refers to the PVA-based resin having the largest content among the PVA-based resins.

[0104] When there are two or more PVA resins that are the main component, i.e., the PVA resin with the largest content in the PVA resin, in the same content, and any one of the PVA resins is used as the main component of the PVA resin (A), i.e., the first PVA resin (a1), the other PVA resins that satisfy the relationship (α) are the second PVA resin (a2), and the other PVA resins that do not satisfy the relationship (α) are the third PVA resin (a3). That is, when any one of the PVA resins is used as the first PVA resin (a1), it is preferred that the first PVA resin (a1) contains a PVA resin that satisfies the aforementioned (α). At this time, when another PVA resin is used as the first PVA resin (a1), the other PVA resins may also contain a second PVA resin (a2) that satisfies the relationship (α) (the PVA resin is the second PVA resin (a2)), and the other PVA resins that do not satisfy the relationship (α) are the third PVA resin (a3).

[0105] In addition, the second PVA resin (a2) refers to a PVA resin that satisfies the above-mentioned (α) in the relationship with the first PVA resin (a1), and the second PVA resin (a2) can be used alone or in combination of two or more. That is, when the PVA resin (A) contains three or more PVA resins, the second PVA resin (a2) can contain only one or two or more. When containing two or more, it is sufficient for each of the first PVA resins (a1) to satisfy the above-mentioned (α).

[0106] In addition, the third PVA resin (a3) ​​is selected from unmodified PVA and modified PVA resins, and refers to a PVA resin having at least one of an average saponification degree, viscosity, modification type, and modification amount different from the first PVA resin (a1) and the second PVA resin (a2). The third PVA resin can be used alone or in combination of two or more.

[0107] The viscosity of a 4 mass % aqueous solution of the first PVA-based resin (a1) at 20° C. is particularly preferably 5 to 50 mPa·s, more preferably 15 to 45 mPa·s, particularly preferably 17 to 40 mPa·s, particularly preferably 21 to 35 mPa·s, and further preferably 21.5 to 30 mPa·s.

[0108] When the viscosity is within this range, the film formability becomes more excellent. When the viscosity is too low, the strength of the water-soluble film as a packaging material tends to decrease, while when it is too high, the viscosity of the aqueous solution during film formation tends to be high and the productivity tends to decrease.

[0109] The viscosity of a 4 mass % aqueous solution of the second PVA-based resin (a2) at 20°C is particularly preferably 10 to 60 mPa·s, more preferably 15 to 55 mPa·s, particularly preferably 17 to 50 mPa·s, particularly preferably 21 to 48 mPa·s, and further preferably 22 to 45 mPa·s.

[0110] When the viscosity is within this range, the film has better formability. If the viscosity is too low, the strength of the water-soluble film as a packaging material tends to decrease, or the film tends to dissolve too quickly when formed into a package. On the other hand, if the viscosity is too high, the viscosity of the aqueous solution during film formation tends to be high, thereby reducing productivity.

[0111] The content mass ratio of the PVA resin (a1) to the PVA resin (a2) (PVA resin (a1) / PVA resin (a2)) is preferably 95 / 5 to 60 / 40, particularly preferably 94 / 6 to 70 / 30, and further preferably 93 / 7 to 80 / 20.

[0112] When the content ratio of the PVA-based resin (a2) is too low, the water-sealing property tends to decrease, or the dissolution of the packaging body tends to become too rapid, and the followability during film molding tends to decrease. When the content ratio of the PVA-based resin (a1) is too low, the solubility tends to decrease over time.

[0113] The average saponification degree of the PVA resin (a1) is preferably 80 mol% or more, particularly preferably 85 to 99 mol%, and further preferably 90 to 98 mol%. If the average saponification degree is too low, the solubility of the water-soluble film in water tends to decrease. It should be noted that even if the average saponification degree is too high, the solubility in water tends to decrease.

[0114] The average saponification degree of the PVA-based resin (a2) is preferably 80 mol% or more, particularly preferably 82 to 99 mol%, and further preferably 85 to 90 mol%. If the average saponification degree is too low, the solubility of the water-soluble film in water tends to decrease. In addition, the uniform stretchability of the film tends to decrease, and the dissolution of the packaging body tends to become too fast. It should be noted that even if the average saponification degree is too large, the solubility in water tends to decrease.

[0115] The absolute value of the difference in average saponification degree between the PVA-based resin (a1) and the PVA-based resin (a2) is preferably 8 mol% or less, more preferably 7 mol% or less.

[0116] When the difference in the average saponification degree is too large, the mechanical properties of the film are deteriorated, the uniform stretchability of the film is deteriorated, and the dissolution of the package body tends to be too rapid.

[0117] The aforementioned PVA resin (a1) and PVA resin (a2) may be: (1) both PVA resin (a1) and PVA resin (a2) are modified PVA resins; (2) PVA resin (a1) is a modified PVA resin and PVA resin (a2) is an unmodified PVA; (3) both PVA resin (a1) and PVA resin (a2) are unmodified PVA, etc. In terms of the stability of the solubility of the film over time, PVA resin (a1) is preferably a modified PVA resin. In terms of the water-sealing property of the film and the followability of the film during molding, (2) is preferred. It is particularly preferred that the PVA resin (a1) contains a modified PVA resin having an anionic group and the PVA resin (a2) contains an unmodified PVA. It is particularly preferred that the PVA resin (a1) contains a modified PVA resin having a carboxyl group and the PVA resin (a2) contains an unmodified PVA.

[0118] The modification amount of the modified PVA-based resin in (1) or (2) is preferably 1 to 15 mol%, more preferably 1.5 to 12 mol%, particularly preferably 2 to 8 mol%, and particularly preferably 2 to 4 mol%.

[0119] If the modification amount is too small, the solubility of the film in water tends to decrease, and if it is too large, the productivity of the PVA-based resin tends to decrease, or the biodegradability tends to decrease, and the film tends to easily cause blocking.

[0120] 〔Plasticizer (B)〕

[0121] The present water-soluble film preferably contains a plasticizer (B) from the viewpoint of imparting appropriate flexibility to the film when formed into a package. The plasticizer (B) may be used alone or in combination of two or more.

[0122] Examples of the plasticizer (B) include glycerols such as glycerol, diglycerol, and triglycerol, alkylene glycols such as triethylene glycol, polyethylene glycol, polypropylene glycol, dipropylene glycol, and propylene glycol, trimethylolpropane, sorbitol, xylitol, and maltitol, etc. Among them, glycerol, polyethylene glycol, and diglycerol are preferably used because they are easily available and can provide a plasticizing effect in a small amount.

[0123] In the present water-soluble film, from the perspective of the mold followability and mechanical properties during the film molding, it is preferred to use a polyol (b1) having a melting point of 50°C or less (hereinafter, sometimes referred to as "plasticizer (b1)". As the polyol (b1) having a melting point of 50°C or less, aliphatic alcohols can be listed, for example, preferably ethylene glycol (-13°C), diethylene glycol (-11°C), triethylene glycol (-7°C), propylene glycol (-59°C), tetraethylene glycol (-5.6°C), 1,3-propanediol (-27°C), 1,4-butanediol (20°C), 1,6-hexanediol (40°C), tripropylene glycol, diols such as polyethylene glycol having a molecular weight of 2000 or less, glycerol (18°C), diglycerol, triethanolamine (21°C) and other trivalent or higher alcohols. These can be used alone or in combination of two or more. It should be noted that the () indicates the melting point. Among the above, from the viewpoint of the flexibility of the water-soluble film, the melting point is particularly preferably 30°C or lower, and more preferably 20°C or lower. The lower limit of the melting point is usually -80°C, preferably -10°C, and particularly preferably 0°C.

[0124] Furthermore, in the plasticizer (b1), the number of hydroxyl groups in one molecule is preferably 4 or less, and particularly preferably 3 or less from the viewpoint of easy control of flexibility at around room temperature (25° C.). Specifically, for example, glycerin is suitable.

[0125] The plasticizer (b1) preferably has a molecular weight of 100 or less, particularly preferably 50 to 100, and further preferably 60 to 95, from the viewpoint of easy control of flexibility. Specifically, for example, glycerin is suitable.

[0126] In addition, when two or more plasticizers (B) are used in combination in the present water-soluble film, it is preferred to use a polyol (b2) having a melting point of 80°C or above (hereinafter sometimes referred to as "plasticizer (b2)") from the aspects of the toughness of the water-soluble film and the shape stability over time when made into a package.

[0127] As the polyol (b2) having a melting point of 80°C or higher, various sugar alcohols, monosaccharides, and polysaccharides can be used, among which, for example, diols such as salicyl alcohol (83°C), catechol (105°C), resorcinol (110°C), hydroquinone (172°C), bisphenol A (158°C), bisphenol F (162°C), and neopentyl glycol (127°C), triols such as phloroglucinol (218°C), erythritol (121°C), threitol (8 8℃), tetrahydric alcohols such as pentaerythritol (260℃), pentahydric alcohols such as xylitol (92℃), arabitol (103℃), fucitol (153℃), glucose (146℃), fructose (104℃), pentahydric alcohols such as mannitol (166℃), sorbitol (95℃), inositol (225℃), hexahydric alcohols such as lactitol (146℃), sucrose (186℃), trehalose (97℃), octahydric alcohols such as maltitol (145℃), and nine or more hydration alcohols. These can be used alone or in combination of two or more. It should be noted that the () indicates the melting point.

[0128] Among the above, from the viewpoint of the tensile strength of the water-soluble film, the melting point is preferably 85°C or higher, and particularly preferably 90°C or higher. The upper limit of the melting point is preferably 300°C, and particularly preferably 200°C.

[0129] Furthermore, in the plasticizer (b2), from the perspective of compatibility with the PVA-based resin (A), the number of hydroxyl groups in one molecule is preferably 4 or more, particularly preferably 5 to 10, and further preferably 6 to 8. Specifically, for example, suitable examples include sorbitol, sucrose, trehalose, and the like.

[0130] The plasticizer (b2) preferably has a molecular weight of 150 or more, particularly preferably 160 to 500, and further preferably 180 to 400, from the viewpoint of toughness of the water-soluble film. Specific suitable examples include sorbitol and sucrose.

[0131] The content of the plasticizer (B) used in the present water-soluble film is preferably 3 to 25 parts by mass, more preferably 5 to 22 parts by mass, particularly preferably 7 to 20 parts by mass, further preferably 8 to 18 parts by mass, and particularly preferably 8.5 to 16 parts by mass, relative to 100 parts by mass of the PVA-based resin (A).

[0132] When the content of the plasticizer (B) is too small, the mechanical properties tend to be insufficient, the film becomes too hard, or becomes brittle in a low-humidity environment, or the conformability of the film during molding decreases, resulting in a poor appearance of the package, or the tension of the package decreases over time.

[0133] On the other hand, when the amount is too large, the film tends to become too soft and easily cause blocking, or the dimensional stability of the package tends to decrease.

[0134] The content of the polyol (b1) is preferably 3 to 25 parts by mass, particularly preferably 5 to 20 parts by mass, further preferably 7 to 18 parts by mass, particularly preferably 8 to 16 parts by mass, based on 100 parts by mass of the PVA-based resin (A).

[0135] When the content of the polyol (b1) is too small, the mechanical properties may be reduced, or the conformability during film molding may be reduced, which may result in a tendency for the appearance of the package to be deteriorated.

[0136] The content of the polyol (b1) is preferably more than 50% by mass, particularly preferably 70% by mass or more, further preferably 80% by mass or more, particularly preferably 85% by mass or more, further preferably 90% by mass or more, and preferably 97% by mass or more, based on the total amount of the plasticizer (B).

[0137] When the content of the polyol (b1) is too small, the mechanical properties may be reduced, or the conformability during film molding may be reduced, which may result in a tendency for the appearance of the package to be deteriorated.

[0138] When the plasticizer (b2) is used, the content is preferably 1 to 10 parts by mass, particularly preferably 1.5 to 8 parts by mass, and further preferably 2 to 6 parts by mass, based on 100 parts by mass of the PVA-based resin (A).

[0139] If the content of the plasticizer (b2) is too low, the tension of the film when formed into a package tends to decrease, while if it is too high, the mechanical properties of the film and the followability during molding tend to decrease, and the appearance of the package tends to deteriorate.

[0140] 〔Packing (C)〕

[0141] The present water-soluble film may further contain a filler (C) as necessary.

[0142] The filler (C) is contained for the purpose of anti-blocking, and examples thereof include organic fillers and inorganic fillers, and among them, organic fillers are preferably used. These can be used alone or in combination of two or more.

[0143] The average particle size of the filler (C) is preferably 0.1 to 50 μm, particularly preferably 1 to 35 μm. It should be noted that the average particle size of the filler (C) is a value measured by a laser diffraction particle size distribution measuring device and is calculated based on the D50 value (particle size at cumulative 50%) of the obtained cumulative volume distribution.

[0144] The organic filler used in the present water-soluble film refers to a granular substance (primary particle) composed of an organic compound and having any shape such as needles, rods, layers, scales, or spheres, or an aggregate of the granular substance (secondary particle).

[0145] As the above-mentioned organic filler, it is mainly selected from polymer compounds, for example, melamine resin, poly(methyl)acrylate resin, polystyrene resin, and biodegradable resins such as starch and polylactic acid can be listed. These can be used alone or in combination of two or more. Among these, poly(methyl)acrylate resin, polystyrene resin, starch, and other biodegradable resins are preferred, and starch is preferred in particular from the aspect of dispersibility for PVA resin (A) and the like.

[0146] As the aforementioned starch, for example, raw starch (corn starch, potato starch, sweet potato starch, wheat starch, cassava starch, sago starch, tapioca starch, sorghum starch, rice starch, bean starch, kudzu starch, fern starch, lotus seed starch, water chestnut starch, etc.), physically modified starch (α-starch, fractionated straight chain starch, wet heat treated starch, etc.), enzyme modified starch (hydrolyzed dextrin, enzymatically decomposed dextrin, straight chain starch, etc.), chemically decomposed modified starch (acid treated starch, hypochlorous acid oxidized starch, dialdehyde starch, etc.), chemically modified starch derivatives (esterified starch, etherified starch, cationized starch, cross-linked starch, etc.), etc. can be listed. These can be used alone or in combination of two or more. Among them, from the aspects of easy availability and economy, raw starch is preferably used, and corn starch and rice starch are particularly preferably used.

[0147] The average particle size of the organic filler is preferably 3 to 50 μm, particularly preferably 10 to 40 μm, and further preferably 15 to 35 μm.

[0148] If the average particle size is too small, the blocking property of the film tends to increase, while if it is too large, fillers tend to aggregate with each other, resulting in reduced dispersibility, or pinholes tend to be formed during film molding or stretching.

[0149] The inorganic filler used in the present water-soluble film refers to a granular substance (primary particle) composed of an inorganic compound and having any shape such as needles, rods, layers, scales, or spheres, or an aggregate of the granular substance (secondary particle).

[0150] Examples of the inorganic filler include oxide-based inorganic compounds such as silica (silicon dioxide), diatomaceous earth, titanium oxide, calcium oxide, magnesium oxide, aluminum oxide, barium oxide, germanium oxide, tin oxide, and zinc oxide, talc, clay, kaolin, mica, asbestos, gypsum, graphite, glass balloons, glass beads, calcium sulfate, barium sulfate, ammonium sulfate, calcium sulfite, calcium carbonate, whisker-like calcium carbonate, magnesium carbonate, dawsonite, dolomite, potassium titanate, carbon black, glass fiber, aluminum oxide fiber, boron fiber, processed mineral fiber, carbon fiber, carbon hollow sphere, bentonite, montmorillonite, copper powder, sodium sulfate, potassium sulfate, zinc sulfate, copper sulfate, iron sulfate, magnesium sulfate, aluminum sulfate, potassium aluminum sulfate, ammonium nitrate, sodium nitrate, potassium nitrate, aluminum nitrate, ammonium chloride, sodium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium phosphate, and potassium chromate. These may be used alone or in combination of two or more.

[0151] Among the above, oxide-based inorganic compounds and talc are preferably used, titanium oxide, talc, and silicon dioxide are more preferably used, and silicon dioxide is particularly preferably used.

[0152] The average particle size of the inorganic filler is preferably 1 to 20 μm, particularly preferably 2 to 15 μm, and further preferably 3 to 10 μm. If the average particle size is too small, the film's stickiness tends to increase, and the film's flexibility and toughness tend to decrease. If it is too large, the water-sealing property tends to decrease.

[0153] The content of the filler (C) is preferably 1 to 30 parts by mass, particularly preferably 2 to 25 parts by mass, and further preferably 2.5 to 20 parts by mass relative to 100 parts by mass of the PVA-based resin (A). When the above content ratio is too small, there is a tendency for the adhesion to increase, and when it is too large, there is a tendency for the softness and toughness of the film to decrease.

[0154] In addition, from the viewpoint of the balance between the blocking resistance of the film and the appearance (transparency, gloss, etc.) when made into a package, and the balance between the blocking resistance of the film and the formability, the content is preferably 8 parts by mass or less, particularly preferably 6 parts by mass or less, and further preferably 0.1 to 5.5 parts by mass, 0.5 to 5.0 parts by mass, 1 to 4.5 parts by mass, 1.5 to 4.0 parts by mass, and 2 to 3.5 parts by mass, relative to 100 parts by mass of the PVA-based resin (A).

[0155] In the present water-soluble film, the mass content ratio (B) / (C) of the plasticizer (B) and the filler (C) is preferably 1.5 to 25, particularly preferably 1.8 to 20, further preferably 2.0 to 18, and particularly preferably 2.5 to 15.

[0156] By setting the content ratio within this range, the followability to the mold can be improved without impairing the mechanical properties of the film.

[0157] It should be noted that when the above-mentioned content ratio is too small (more filler and less plasticizer), the film's followability to the mold becomes insufficient and the appearance of the molded package tends to deteriorate. When it is too large (less filler and more plasticizer), the film's blocking resistance and mechanical properties tend to decrease.

[0158] 〔Surfactant (D)〕

[0159] The present water-soluble film may contain a surfactant (D) as necessary.

[0160] As surfactant (D), it is contained for the purpose of improving the peelability of the self-casting surface when manufacturing this water-soluble film, and nonionic surfactant, cationic surfactant, anionic surfactant etc. can be listed. For example, polyoxyethylene nonylphenyl ether, polyoxyethylene octyl nonyl ether, polyoxyethylene dodecyl phenyl ether, polyoxyethylene alkyl allyl ether, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene alkyl ether phosphate ester monoethanolamine salt, polyoxyethylene lauryl amino ether, polyoxyethylene stearyl amino ether and other polyoxyethylene alkyl amino ethers etc. can be listed, and one kind or two or more kinds can be used in combination. Among them, from the aspect of manufacturing stability, polyoxyethylene alkyl ether phosphate ester monoethanolamine salt and polyoxyethylene lauryl amino ether are suitable.

[0161] The content of the surfactant (D) is preferably 0.1 to 5 parts by mass, particularly preferably 0.2 to 4.5 parts by mass, and further preferably 0.3 to 4 parts by mass, relative to 100 parts by mass of the PVA-based resin (A). If the content is too low, the peeling property between the casting surface of the film-forming device and the water-soluble film to be formed tends to decrease, thereby reducing productivity. If the content is too high, there tends to be a tendency to produce disadvantages such as reduced adhesive strength during sealing when the water-soluble film is formed into a package.

[0162] It should be noted that, in the present water-soluble film, in the range that does not hinder the purpose of the invention, it is preferred to further mix an antioxidant in terms of inhibiting yellowing. As the above-mentioned antioxidant, for example, sulfites such as sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, tartaric acid, ascorbic acid, sodium thiosulfate, catechol, Rongalite, etc. can be listed. These can be used alone or in combination of two or more. Among them, sulfites are preferred, and sodium sulfite is particularly preferred. The blending amount of the antioxidant is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and particularly preferably 0.3 to 3 parts by mass relative to 100 parts by mass of the PVA-based resin (A).

[0163] In addition, the present water-soluble film may further contain fragrances, rust inhibitors, mildew inhibitors, colorants, extenders, defoamers, ultraviolet absorbers, fluorescent whitening agents, liquid paraffins, bitter ingredients (e.g., denatonium benzoate, etc.), etc., within the scope that does not hinder the purpose of the invention. These may be used alone or in combination of two or more.

[0164] <Manufacturing of water-soluble films>

[0165] In the present water-soluble film, the aforementioned PVA-based resin (A) is compounded, preferably further compounded with a plasticizer (B), and further compounded with a filler (C) and a surfactant (D) as required, dissolved or dispersed in water to prepare a film-forming raw material, and then formed into a water-soluble film. The process of manufacturing the present water-soluble film is described below.

[0166] 〔Dissolution process〕

[0167] In the dissolving step, the PVA-based resin composition composed of the components blended above is dissolved or dispersed using water to prepare an aqueous solution or aqueous dispersion to be a film-forming raw material.

[0168] As a dissolution method when dissolving the PVA-based resin composition in water, room temperature dissolution, high temperature dissolution, pressure dissolution, etc. are generally used. Among them, high temperature dissolution is preferred from the viewpoint of less undissolved matter and excellent productivity.

[0169] The solid content concentration of the film-forming raw material is preferably 10 to 65% by mass, particularly preferably 12 to 50% by mass, and further preferably 15 to 40% by mass. If the concentration is too low, the productivity of the film tends to decrease, and if it is too high, the viscosity becomes too high, defoaming of the film-forming raw material takes time, or a parting line tends to be generated during film formation.

[0170] [Film-making process]

[0171] In the film forming step, the film forming raw material prepared in the dissolving step is formed into a film shape and, if necessary, dried, thereby preparing the present water-soluble film having a water content of less than 15% by mass.

[0172] When forming a film, for example, a method such as a melt extrusion method or a casting method can be used. From the viewpoint of the accuracy of the film thickness, the casting method is preferred.

[0173] When the casting method is carried out, for example, the aforementioned film-making raw material is ejected from a slit such as a T-shaped slit die, cast on a casting surface such as an endless belt, a metal surface of a drum, a polyethylene terephthalate film, a plastic substrate such as polypropylene, and dried, thereby being able to produce the present water-soluble film.

[0174] In the film-forming step, the present water-soluble film peeled from the casting surface or the like after drying is conveyed and wound up, and then wound around a core tube to prepare a film roll.

[0175] The obtained film roll may be supplied directly as a product, but may also be supplied preferably in the form of a film roll cut into a film width of a desired size.

[0176] In this manner, the present water-soluble film can be produced.

[0177] The thickness of the water-soluble film is appropriately selected according to the application, and is preferably 10 to 130 μm, particularly preferably 20 to 110 μm, further preferably 30 to 100 μm, and particularly preferably 45 to 90 μm. If the thickness is too thin, the mechanical strength of the film tends to decrease, and if it is too thick, the dissolution rate in water tends to slow down, and the film-forming efficiency tends to decrease.

[0178] The width of the water-soluble film is appropriately selected according to the application, and is preferably 300 to 5000 mm, particularly preferably 500 to 4000 mm, and further preferably 600 to 3000 mm. If the width is too narrow, production efficiency tends to decrease, and if it is too wide, it tends to become loose and difficult to control film thickness.

[0179] The length of the water-soluble film is appropriately selected according to the application, and is preferably 100 to 20,000 m, particularly preferably 800 to 15,000 m, and further preferably 1,000 to 10,000 m. If the length is too short, it tends to take time to switch the film, and if it is too long, it tends to be too tight to have a poor appearance and too heavy a quality.

[0180] In addition, the surface of the water-soluble film can be smooth, but from the perspective of blocking resistance, slippage during processing, reduced adhesion between products and appearance, it is also preferred to pre-process one or both sides of the film with embossed patterns, fine concave-convex patterns, special engraved patterns, etc.

[0181] In addition, from the perspective of mechanical strength and heat sealability, the water content of the water-soluble film is preferably 3 to 15% by mass, particularly preferably 5 to 10% by mass, and further preferably 6 to 8% by mass. When the above water content is too low, the film tends to become too hard, the formability when made into a package, the impact resistance of the package, or the sealing tends to become poor, and when it is too high, there is a tendency for easy blocking. When adjusting to the above water content, it can be achieved by appropriately setting the drying conditions and the humidity control conditions.

[0182] In addition, the said water content is measured based on JIS K 6726 3.4, and the value of the volatile matter obtained is made into the water content.

[0183] It is important that the water-soluble film thus obtained satisfies the above-mentioned specific elastic modulus. In order to adjust the above-mentioned elastic modulus to the above-mentioned range, for example, the following methods can be cited: (1) a method of relatively reducing the total amount of plasticizer (B) and increasing the proportion of plasticizer (b1); (2) a method of adjusting the content ratio of plasticizer and filler, etc. Among them, the method (1) is preferred from the aspect of being able to control the above-mentioned physical properties while maintaining various physical properties of the water-soluble film.

[0184] The water-soluble film is useful for various packaging purposes such as unit packaging of pesticides, detergents and other drugs, (hydraulic) transfer films, sanitary products such as napkins and diapers, pollutant treatment products such as ostomy bags, medical products such as blood-absorbing sheets, temporary base materials such as seedling sheets, seed tapes and embroidery base fabrics, etc. In particular, it can be suitably used for unit packaging of drugs such as detergents for washing and dishwashing detergents.

[0185] <Medicine packaging>

[0186] The medicine package body as one embodiment of the present invention is a package body formed by the present water-soluble film and encapsulating medicines, etc. The independent package body maintains the shape of the encapsulated medicines, etc. during storage. In addition, when using, the entire package body is put into water, the independent package body (the present water-soluble film) contacts with water and the independent package body (the present water-soluble film) dissolves, and the medicines, etc. are dissolved or dispersed in the water from the independent package body, and the effect of the medicine is exerted.

[0187] As the encapsulated agent, for example, pesticides such as insecticides, fungicides, herbicides, fertilizers, detergents, etc. can be listed, and detergents such as washing detergents and dishwashing detergents are particularly preferred. The agent can be in the form of a liquid, a solid, or a gel. In the case of a liquid, it is in a liquid state. In the case of a solid, it can be in a granular state, a tablet state, a powder state, etc. The agent is preferably a drug used by dissolving or dispersing in water, and is particularly useful for packaging liquid detergents. In addition, the pH of the agent can also be any of alkaline, neutral, and acidic.

[0188] The pH value of the liquid detergent is preferably 6 to 12, particularly preferably 6.5 to 11, and more preferably 7 to 8. In addition, the water content of the liquid detergent is preferably 15% by mass or less, particularly preferably 0.1 to 10% by mass, and more preferably 0.1 to 7% by mass. When it is within the above range, the water-soluble film does not gel or become insoluble, and the water solubility becomes excellent.

[0189] The pH value is measured in accordance with JIS K 3362 8.3. The water content is measured in accordance with JIS K 3362 7.21.3.

[0190] The viscosity of the liquid detergent is not particularly limited as long as it is fluid and changes shape depending on the container, but is preferably 10 to 200 mPa·s. The viscosity of the liquid detergent is measured by a B-type rotational viscometer at room temperature.

[0191] When using the present water-soluble film to package liquid detergents and other drugs to form a drug package, a known method can be used. For example, the following manufacturing method can be cited, which is a method for manufacturing a drug package using two or more water-soluble films, in which a first water-soluble film is vacuum-formed using a mold, a drug is put into the first water-soluble film formed by the vacuum forming, and the first water-soluble film formed is attached to another second water-soluble film to package the drug to manufacture the drug package, and the present water-soluble film is used as the first water-soluble film.

[0192] The first water-soluble film may also be a water-soluble film formed by laminating two or more water-soluble films. In addition, at least one layer or all layers of the first water-soluble film formed by laminating two or more water-soluble films may be the present water-soluble film, and preferably all layers are the present water-soluble film. It should be noted that the number of layers of the first water-soluble film formed by laminating two or more water-soluble films is usually 3 or less.

[0193] In addition, the second water-soluble film may be the present water-soluble film or other water-soluble films, but is preferably the present water-soluble film. Specifically, for example, the second water-soluble film may be a water-soluble film whose initial elastic modulus is not within the range of 2.5 to 10 MPa, but the present water-soluble film is preferably used. In addition, the second water-soluble film may also be a water-soluble film formed by stacking more than two water-soluble films. In addition, the second water-soluble film formed by stacking more than two water-soluble films preferably has at least one layer or all layers as the present water-soluble film, and preferably all layers as the present water-soluble film. It should be noted that the number of layers of the second water-soluble film formed by stacking more than two water-soluble films is usually 3 or less.

[0194] According to the manufacturing method using the present water-soluble film, even in the case of deep drawing such that the thickness of the thinnest part of the aforementioned first water-soluble film is less than 35% or less than 30% of the thickness of the first water-soluble film before mold forming, a water-soluble film with excellent followability can be obtained, and by using the above-mentioned water-soluble film to form a packaging body, a packaging body with excellent appearance that has tension, is free of deformation, and is free of wrinkles can be obtained.

[0195] More specifically, the packaging body using the present water-soluble film is manufactured by laminating two sheets of the present water-soluble film, fixing the film (bottom film) on a mold located at the bottom of a molding device, and also fixing a film (top film) on the top of the device. The bottom film is heated by a dryer, a hot roller, etc., and vacuum-formed in the mold. Then, after a liquid detergent or other agent is added to the formed film, the top film and the bottom film are crimped. After crimping, the vacuum is released to obtain a packaging body.

[0196] Examples of methods for crimping a film include: (1) a heat sealing method; (2) a water sealing method; and (3) a glue sealing method. Among them, the water sealing method (2) has the advantage of being versatile and having excellent productivity.

[0197] The mold may be of various sizes and shapes depending on the type and purpose of the medicine, and may have multiple partitions.

[0198] It should be noted that, generally, when forming a package, deep drawing is performed when the film is stretched 2.5 times or more and the thinnest part thickness of the package is 35% or less, preferably 30% or less of the original film thickness.

[0199] The surface of the aforementioned pharmaceutical packaging body can generally be listed as smooth. From the perspective of anti-sticking, slippage during processing, reduced adhesion between products (packaging bodies) and appearance, the outer surface of the packaging body (the present water-soluble film) can also be subjected to embossed patterns, fine concave-convex patterns, special engraved patterns, and other concave-convex processing.

[0200] The drug retention time (time until the bag is broken) of the drug package is usually more than 30 seconds. The upper limit depends on the type of drug and the method of use, and in the case of a liquid detergent package for washing, it is usually preferably 300 seconds or less.

[0201] The rupture time of the drug package is obtained by leaving the drug package to stand at 23°C and 50% RH for 1 day, floating it in ion exchange water at 20°C, and measuring the time required until the package is ruptured and the drug begins to leak.

[0202] The shape of the medicine package can be appropriately selected without particular limitation, and may be, for example, a roughly cubic shape, a roughly spherical shape, a roughly flat spherical shape, a roughly teardrop shape, etc., and may have a plurality of partitions.

[0203] The number of the plurality of partitions in the drug package can be appropriately selected according to the type of drug, etc., and is not particularly limited, and is, for example, 2 to 10 partitions, preferably 3 to 8 partitions, and more preferably 4 to 6 partitions. In addition, the plurality of partitions preferably package different types of drugs according to the partitions.

[0204] The dimensions (volume, length, width, thickness) of the medicine packaging body can be appropriately selected, and the volume of the contents can also be appropriately selected.

[0205] For example, the volume of the drug package is usually 1 to 50 mL, preferably 5 to 45 mL, and particularly preferably 10 to 40 mL.

[0206] The thickness of the medicine package is usually 0.5 to 60 mm, preferably 5 to 50 mm, and more preferably 10 to 40 mm.

[0207] The length of the medicine package is usually 10 to 80 mm, preferably 15 to 70 mm, and more preferably 20 to 60 mm.

[0208] The width of the medicine package is usually 10 to 80 mm, preferably 15 to 70 mm, and more preferably 20 to 60 mm.

[0209] Example

[0210] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to the following Examples unless the gist of the present invention is exceeded. In the examples, "parts" and "%" are based on mass.

[0211] As material components of the water-soluble film, the following substances were prepared.

[0212] Modified PVA resin (a1): a carboxyl-modified PVA resin having a viscosity of 22 mPa·s in a 4% by mass aqueous solution at 20° C., an average saponification degree of 94 mol %, and a modification amount of 2.2 mol % based on monomethyl maleate

[0213] Unmodified PVA (a2): Unmodified PVA having a 4% by mass aqueous solution viscosity of 43 mPa·s at 20°C and an average saponification degree of 88 mol%

[0214] Plasticizer (b1): glycerol

[0215] Filler (c1): corn starch (average particle size 20 μm)

[0216] Surfactant (d1): Polyoxyalkylene alkyl ether phosphate monoethanolamine salt

[0217] <Example 1>

[0218] 90 parts of modified PVA resin (a1) as PVA resin (A), 10 parts of unmodified PVA (a2), 18 parts of glycerol (b1) as plasticizer (B), 2 parts of corn starch (c1) as filler (C), 0.2 parts of polyoxyalkylene alkyl ether phosphate monoethanolamine salt (d1) as surfactant (D) and water are mixed and dissolved to obtain an aqueous dispersion of a resin composition having a solid content concentration of 28%, i.e., a film-forming raw material.

[0219] The obtained film-forming raw material was cast on a polyethylene terephthalate film and passed through a drying chamber (105° C.) of 3 m in length at a rate of 0.66 m / min for drying to obtain a water-soluble film having a thickness of 76 μm and a moisture content of 8.5%.

[0220] <Examples 2 to 6, Comparative Example 1>

[0221] In Example 1, the same procedure was carried out except that the composition was changed as shown in Table 1 to obtain a water-soluble film.

[0222] The water-soluble films obtained in Examples 1 to 6 and Comparative Example 1 were used to evaluate the films according to the following method. The results are shown in Table 1. In Table 1, "-" means that the films were not evaluated.

[0223] [Initial elastic modulus obtained by tensile creep test using a dynamic viscoelasticity measuring device]

[0224] The initial elastic modulus obtained by the tensile creep test using a dynamic viscoelasticity measuring device is measured and calculated as follows. That is, the water-soluble film obtained in the above-mentioned is left to stand for 24 hours under an environment of 23°C and 40% RH, and then cut into 60 mm in the flow direction (MD) and 5 mm in the width direction (TD) to obtain a measurement sample. For the obtained measurement sample, the elastic modulus is measured and calculated under the following conditions using a dynamic viscoelasticity measuring device "DMAQ800" (manufactured by TA Instruments Japan).

[0225] [Setting conditions]

[0226] Chuck spacing: 5mm

[0227] Film width: 5mm

[0228] Measurement (setting) temperature: 30°C

[0229] Measurement mode: DMA Creep

[0230] Load: 16.1MPa

[0231] Hold time: 0.5 minutes

[0232] Cool-down time: 5 minutes

[0233] [Calculation method]

[0234] The initial (0.004 minutes after the start of the measurement) elastic modulus (MPa) was calculated using the following method. That is, the strain (ε) was calculated based on the length of the film at the start of the measurement (L0) and the length of the film 0.004 minutes after the start of the measurement (L) (strain (ε) = (L-L0) × 100 / L0). The elastic modulus was calculated using the strain (ε) obtained here and the set load of 16.1 MPa. (Elastic modulus (MPa) = 16.1 / strain (ε)).

[0235] 〔Followability〕

[0236] The water-soluble film (thickness 76 μm) obtained above was left to stand at 23° C. and 40% RH for 24 hours, and then a packaging body was produced using a packaging body production machine manufactured by Engel according to the following procedure. Whether the film followed the mold was visually evaluated.

[0237] That is, a water-soluble film (bottom film) was fixed on a mold located at the bottom of the device (the size of the package to be formed: about 45 mm in length, about 42 mm in width, and about 36 mm in height), and a water-soluble film (top film) was also fixed on the top of the device. Then, the bottom film was vacuum-formed in the mold, and whether it followed the mold was evaluated.

[0238] Then, 0.25 g of water was applied to the entire surface of the top film (80 mm in length and 140 mm in width), and the top film and the bottom film were pressed together. After 10 seconds of pressing, the vacuum was released to obtain a package body without encapsulated material (thinnest part film thickness: 25 μm).

[0239] [Evaluation criteria]

[0240] ○ (very good) ... The film follows the mold well in less than 30 seconds.

[0241] △ (good) ... A slight gap was observed between the film and the mold, or it took 30 seconds or more to sufficiently follow the mold.

[0242] × (poor) ... The film obviously floats on the mold and does not follow it.

[0243] [Appearance]

[0244] In addition, the appearance of the package produced in the above-mentioned evaluation of "Followability" was visually observed and evaluated.

[0245] [Evaluation criteria]

[0246] ○ (very good) ... No deformation or wrinkles were observed on the package.

[0247] ×(poor)…Deformation and wrinkles were observed on the package.

[0248] 〔Mechanical properties〕

[0249] The water-soluble film obtained above was used to measure tensile strength and tensile elongation according to JIS K 7127. That is, after standing for 24 hours under 23°C, 50% RH humidity conditions before measurement, the water-soluble film was placed under this environment and measured for tensile strength and tensile elongation at a tensile speed of 200 mm / min using Autograph AG-X Plus (manufactured by Shimadzu Corporation) (film width 15 mm, chuck distance 50 mm).

[0250] [Evaluation criteria]

[0251] 〇 (very good) ... tensile strength is 10 MPa or more, and tensile elongation exceeds 300%.

[0252] △ (good) ... The tensile strength is 10 MPa or more, and the tensile elongation is 200% or more and 300% or less.

[0253] × (poor) ... the tensile strength is 0 to less than 10 MPa and / or the tensile elongation is less than 200%.

[0254] 〔Solubility〕

[0255] [Solubility at 20℃]

[0256] The water-soluble film obtained above was cut into a size of 3 cm × 5 cm, placed in a 1-liter beaker filled with water (1 liter), fixed with a clamp, and stirred with a stirrer (rotor length 3 cm, rotation speed 750 rpm) while the water temperature was maintained at 20°C. When no dispersion of insoluble particles with a diameter of more than 1 mm was observed, the film was considered to be dissolved, and the time required for dissolution was evaluated.

[0257] [Evaluation criteria]

[0258] ○(very good)…Dissolved in less than 90 seconds.

[0259] △ (good) ... dissolved in 90 seconds or more and 300 seconds or less.

[0260] ×(poor) ... Not dissolved even after more than 300 seconds.

[0261] [Solubility at 10℃]

[0262] The water-soluble film obtained above was cut into a size of 3 cm × 5 cm, placed in a 1-liter beaker filled with water (1 liter), fixed with a clamp, and stirred with a stirrer (rotor length 3 cm, rotation speed 750 rpm) while the water temperature was maintained at 10°C. When no dispersion of insoluble particles with a diameter of more than 1 mm was observed, the film was considered to be dissolved, and the time required for dissolution was evaluated.

[0263] [Evaluation criteria]

[0264] ◎(excellent)…Dissolves in less than 90 seconds.

[0265] 0 (very good) ... dissolved in 90 seconds or more and less than 120 seconds.

[0266] △ (good) ... dissolved in 120 seconds or more and 300 seconds or less.

[0267] ×(poor) ... Not dissolved even after more than 300 seconds.

[0268] 〔Haze〕

[0269] The water-soluble film obtained above was cut into a size of 5 cm×5 cm, and the haze was measured in accordance with JIS K 7136 using a haze meter NDH4000 (manufactured by Nippon Denshoku Industries Co., Ltd.).

[0270] 〔Glossiness〕

[0271] The water-soluble film obtained above was left to stand at 23° C. and 40% RH for 24 hours, and then a drug package was produced by the following procedure using a packaging machine manufactured by Engel.

[0272] That is, a water-soluble film (bottom film) is fixed on a mold located at the bottom of the device (the size of the formed package body: about 45 mm in length, about 42 mm in width, and about 30 mm in height), and a water-soluble film (top film) is also fixed on the top of the device. The bottom film is heated for 4 seconds in a dryer that generates hot air at 70°C, and the bottom film is vacuum-formed in the mold. Then, 25 mL of a commercially available laundry detergent (composition summary: 11% propylene glycol, 7.5% glycerin, 67% surfactant, 14.2% water, pH 7.5) is added to the formed water-soluble film. 0.25 g of water is applied to the entire surface of the top film (80 mm in length and 140 mm in width), and the top film and the bottom film are crimped. After crimping for 10 seconds, the vacuum is released to obtain a liquid detergent packaging body, i.e., a drug packaging body.

[0273] The obtained liquid detergent package was placed on black paper, and the gloss meter micro-TRI-gross (manufactured by BYK-Gardner) was lightly pressed horizontally on the top of the base film side to measure the glossiness. This operation was repeated 10 times and the average value was calculated. The measurement was carried out in accordance with JIS Z 8741 under the conditions of an incident angle of 60°, 23°C, and 40% RH.

[0274] 〔Compression strength〕

[0275] The water-soluble film obtained above was left to stand at 23° C. and 40% RH for 24 hours, and then a drug package was produced by the following procedure using a packaging machine manufactured by Engel.

[0276] That is, a water-soluble film (bottom film) is fixed on a mold located at the bottom of the device (the size of the formed package body: about 45 mm in length, about 42 mm in width, and about 30 mm in height), and a water-soluble film (top film) is also fixed on the top of the device. The bottom film is heated for 4 seconds in a dryer that generates hot air at 70°C, and the bottom film is vacuum-formed in the mold. Then, 25 mL of a commercially available laundry detergent (composition summary: 11% propylene glycol, 7.5% glycerin, 67% surfactant, 14.2% water, pH 7.5) is added to the formed water-soluble film. 0.25 g of water is applied to the entire surface of the top film (80 mm in length and 140 mm in width), and the top film and the bottom film are crimped. After crimping for 10 seconds, the vacuum is released to obtain a liquid detergent packaging body, i.e., a drug packaging body.

[0277] The obtained liquid detergent package was used to evaluate the compressive strength according to the method shown below. The results are shown in Table 1 below.

[0278] [Evaluation method]

[0279] The liquid detergent package produced by the above method was left to stand for 1 hour under 23°C and 40% RH humidity conditions, and then the compressive strength of the liquid detergent package when broken was measured using Autograph AG-X Plus (manufactured by Shimadzu Corporation) at a test speed of 200 mm / min. It should be noted that the load cell used was 5 kN.

[0280] [Evaluation Criteria]

[0281] ○(very good)…Compression strength exceeds 1000N.

[0282] △ (good) ... compression strength is 300N or more and 1000N or less.

[0283] ×(poor)…The compression strength is lower than 300N and the bag is easily broken. Or the bag is easily broken because the sealing surface is easily peeled off.

[0284] [Table 1]

[0285]

[0286] According to the results in Table 1, the water-soluble films of Examples 1 to 6 satisfying the initial elastic modulus specified in the present invention have excellent mold followability and mechanical properties during molding, and the packaging bodies obtained by deep drawing using the films have no deformation, no wrinkles, etc. and excellent appearance, and the compression strength is sufficient, so they are suitable for packaging purposes. It should be noted that in the evaluation of the compression strength of the pharmaceutical packaging body, it can be seen that there is no situation where the sealed surface is easily peeled off and the bag is broken, that is, the water sealing property is also excellent.

[0287] On the other hand, the drug packaging body using the water-soluble film of Comparative Example 1 which did not satisfy the initial elastic modulus specified in the present invention had insufficient followability to the mold, and the obtained packaging body was deformed and had a poor appearance.

[0288] The above embodiments show specific aspects of the present invention, but the above embodiments are merely examples and should not be construed as limiting. It is obvious to those skilled in the art that various modifications are within the scope of the present invention.

[0289] Industrial Applicability

[0290] The water-soluble film of the present invention is excellent in mold followability during molding and can be molded into a package body with excellent appearance. It can be used for various packaging purposes and is particularly useful for unit packaging of medicines and the like.

Claims

1. A water-soluble film, characterized in that: The water-soluble film contains a polyvinyl alcohol-based resin A, and the initial elastic modulus of the water-soluble film obtained by a tensile creep test using a dynamic viscoelasticity measuring device is 2.5 to 10 MPa.

2. The water-soluble film according to claim 1, characterized in that: The polyvinyl alcohol resin A further comprises a plasticizer B, wherein the content of the plasticizer B is 3 to 25 parts by mass based on 100 parts by mass of the polyvinyl alcohol-based resin A.

3. The water-soluble film according to claim 1 or 2, characterized in that: The polyvinyl alcohol-based resin A contains an anionic group-modified polyvinyl alcohol-based resin.

4. The water-soluble film according to claim 1 or 2, characterized in that: The polyvinyl alcohol-based resin A contains a polyvinyl alcohol-based resin a1 as a main component of the component A and a polyvinyl alcohol-based resin a2 that satisfies the following (α) in relation to the component a1: (α) The viscosity of a 4 mass % aqueous solution of the polyvinyl alcohol-based resin a2 at 20°C is higher than the viscosity of a 4 mass % aqueous solution of the polyvinyl alcohol-based resin a1 at 20°C.

5. The water-soluble film according to claim 4, characterized in that: The polyvinyl alcohol-based resin a1 is a modified polyvinyl alcohol-based resin.

6. A medicine packaging body, characterized in that: The invention comprises: a packaging body formed by the water-soluble film according to claim 1 or 2 and a medicine packaged in the packaging body.

7. The medicine packaging body according to claim 6, characterized in that: The medicine package has a plurality of partitions, and medicine is packaged in at least one of the partitions.

8. The medicine packaging body according to claim 6, characterized in that: The agent is a liquid detergent.

9. A method for manufacturing a pharmaceutical packaging body, characterized in that: The invention relates to a method for manufacturing a drug packaging body using two or more water-soluble films. In the method, a first water-soluble film is vacuum-formed using a mold, a drug is put into the first water-soluble film formed by the vacuum forming, and the formed first water-soluble film is bonded to a second water-soluble film to package the drug to manufacture the drug packaging body. The first water-soluble film is the water-soluble film described in claim 1 or 2.

10. The method for manufacturing a medicine package according to claim 9, characterized in that: The film thickness of the thinnest portion of the first water-soluble film formed by the vacuum forming is 35% or less of the film thickness of the first water-soluble film before the vacuum forming.

Citation Information

Patent Citations

  • Water soluble film for thermoforming deep-drawn profiles and thermoformed articles comprising same

    WO2017132540A1